1996
DOI: 10.3109/08820139609059301
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Function in Elderly Persons Assessed by Flow Cytometry

Abstract: It is well known that the immune response declines with senescence and it is suggested that these changes render an individual susceptible to infection, autoimmune phenomena and cancer. Bacterial and viral infections are a major cause of illness and death amongst aged subjects, and once infection is established, the elderly also have a diminished capacity to prevent its spread (1). The cellular and molecular basis for this age-related decline in immunocompetence are still unknown and, possibly, are related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 30 publications
2
47
0
2
Order By: Relevance
“…Research to date suggests that any age-related decline in neutrophil function in healthy elderly individuals is largely due to a decline in phagocytic capacity, because chemotaxis remains largely unaltered in the elderly (MacGregor & Shalit, 1990) and similar data have been obtained for superoxide production in response to fMLP (Esparza et al, 1996;Butcher et al, 2001). Studies measuring phagocytosis of opsonized bacteria or yeast and opsonized zymosan as the neutrophil target have all shown a significant reduction in phagocytic ability in the elderly (Emanuelli et al, 1986;Mege et al, 1988;Esparza et al, 1996;Wenisch et al, 2000;Butcher et al, 2001). We have shown that one of the receptors involved in recognizing antibodies on the surface of bacteria, CD16, is significantly reduced with age and may contribute to the observed decline in neutrophil phagocytic function with age (Butcher et al, 2001).…”
Section: Effect Of Age On Adrenal Hormones and Immune Functionmentioning
confidence: 55%
“…Research to date suggests that any age-related decline in neutrophil function in healthy elderly individuals is largely due to a decline in phagocytic capacity, because chemotaxis remains largely unaltered in the elderly (MacGregor & Shalit, 1990) and similar data have been obtained for superoxide production in response to fMLP (Esparza et al, 1996;Butcher et al, 2001). Studies measuring phagocytosis of opsonized bacteria or yeast and opsonized zymosan as the neutrophil target have all shown a significant reduction in phagocytic ability in the elderly (Emanuelli et al, 1986;Mege et al, 1988;Esparza et al, 1996;Wenisch et al, 2000;Butcher et al, 2001). We have shown that one of the receptors involved in recognizing antibodies on the surface of bacteria, CD16, is significantly reduced with age and may contribute to the observed decline in neutrophil phagocytic function with age (Butcher et al, 2001).…”
Section: Effect Of Age On Adrenal Hormones and Immune Functionmentioning
confidence: 55%
“…Elderly people are more susceptible to infection with various pathogenic organisms than middle-aged or young adults because T-lymphocyte production and proliferation decline with age, resulting in decreased cell-mediated immunity and decreased antibody production to new antigens [30][31][32][33][34]. Additionally, their cardiopulmonary reverse is limited.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Also, reduced phagocytosis has been described in subjects >65 years. 18 Little is known about phagocyte function in stroke, but there are hints that it may also be disturbed. One study reported impaired neutrophil burst in a small cohort of patients with intracranial hemorrhage who required neurosurgical intervention, 19 whereas an earlier report suggested the occurrence of alterations in neutrophil function in patients with stroke, as indicated by measurement of the granulocyte antisedimentation rate.…”
mentioning
confidence: 99%